Monolithic Yb-Doped Femtosecond Fiber Laser With >300 W Average Power - Chenyang Gao; Yang Gui; Yandang Wang; Xianming Zhang; Gengji Zhou; Meng Pang; Jianwu Ding; Yuxin Leng (IEEE Photonics Journal)
In this submission, we report a maximum 638-W fiberized chirped-pulse-amplification (CPA) laser system with a bulk reflection grating compressor. The system is able to emit 338-W compressed pulses of 624 fs centered at 1 µm, corresponding to a pulse energy of 1.3 µJ at a pulse repetition rate of 258 MHz. The output beam quality factor M2 is measured to be <1.3, without observing transverse-mode instability. The standard deviation of the power fluctuation is quantified to be 0.6 W over a time span of more than 1 hour, at an output power of up to 100 W.